1979
DOI: 10.1007/bf01219739
|View full text |Cite
|
Sign up to set email alerts
|

Possible mechanism by which somatostatin-induced glucagon suppression improves glucose tolerance during insulinopaenia in man

Abstract: The present study examines the question of whether lowering the basal plasma glucagon concentration alters the response of the liver to an intravenous glucose load under conditions where insulin is present at near-basal concentrations. Acute hyperglycaemia of 220-240 mg/dl was induced by peripheral venous glucose infusion in two groups of normal men who had undergone hepatic vein catheterization. Somatostatin (0.9 mg/h) was infused in both groups together with an infusion of insulin (0.15 mU/kg/min) to maintai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1981
1981
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…This insulin concentration range is close to the half-maximally effective concentration for suppression of hepatic glucose production (22)(23)(24). Since hepatic accumulation of glycogen might be expected to reflect glucose uptake by the liver (1), the present results are supported by reports on stimulation of net splanchnic glucose uptake during hypoglucagonemia at low plasma insulin concentrations in dogs (25) and healthy humans (26), but even at increased insulin levels in dogs (27).…”
Section: Discussionsupporting
confidence: 80%
“…This insulin concentration range is close to the half-maximally effective concentration for suppression of hepatic glucose production (22)(23)(24). Since hepatic accumulation of glycogen might be expected to reflect glucose uptake by the liver (1), the present results are supported by reports on stimulation of net splanchnic glucose uptake during hypoglucagonemia at low plasma insulin concentrations in dogs (25) and healthy humans (26), but even at increased insulin levels in dogs (27).…”
Section: Discussionsupporting
confidence: 80%
“…Not only is the liver very sensitive to changes in plasma glucagon, it also responds rapidly, with a half-maximal activation time of only 8 minutes (27). Human studies, although less well controlled, confirmed that the observations made in the dog extend to man (22)(23)(24)(25)(28)(29)(30). Thus, it is evident that after an overnight fast, basal levels of glucagon drive resting glucose production, thereby allowing insulin to link hepatic glucose output to the body's need for glucose.…”
Section: Metabolic Credentialsmentioning
confidence: 51%
“…Glucagon also modulates hepatic glucose uptake (HGU) (28,31,32) and hepatic glycogen synthesis (33). A decrease in plasma glucagon has little effect on HGU in the presence of elevated insulin (31), but the effect can be quite marked when insulin is deficient (32), which has obvious implications for diabetes.…”
Section: Metabolic Credentialsmentioning
confidence: 99%
“…These beneficial effects of SST on glucose control were attributed to the ability of SST to suppress glucagon secretion (Liljenquist et al, 1979). Although it has not been directly studied, SST treatment may also improve insulin sensitivity by lowering elevated GH levels, which are known to impair insulin signaling (Takano et al, 2001;Hansen et al, 1986).…”
Section: Type 1 Diabetes Mellitus -Early Studies Have Demonstrated Thmentioning
confidence: 99%